Prevalence and clinical significance of serum anti-cyclic citrullinated peptide antibodies in primary Sjögren's syndrome - Aktan Köşker, Tuğba; Doğan, İsmail; Küçükşahin, Orhan; Erten, Şükran (The European Research Journal, 2022)
Objectives: Although anti-cyclic citrullinated peptide (anti-CCP) antibody is a specific marker for rheumatoid arthritis (RA), it is also detected positively in some other rheumatological diseases including Sjögren's syndrome (SS) and even in healthy people. Studies have shown that anti-CCP guides the early diagnosis, prognosis and treatment of RA patients. SS and RA overlap syndrome are common. This study was conducted to determine the prevalence and clinical significance of serum anti-CCP in primary SS patients followed in our outpatient clinic. Methods: Eighty-two primary SS, 100 RA patients and 100 healthy controls applied to rheumatology outpatient clinic were examined. Patients and control groups were compared in terms of demographic characteristics, laboratory results and anti-CCP. Results: In the present study, anti-CCP was positive in 4 (4.9%) of 82 primary SS patients. In the SS group, among other autoantibodies, ANA was found to be positive at 88.8%, RF 45%, SS-A 64.6%, and SS-B 36.7%. There was no relationship between anti-CCP and joint involvement in patients with SS. Conclusions: Anti-CCP antibody positivity can be found in SS patients. Acute phase proteins may be higher in primary SS patients with positive anti-CCP antibody. However, studies have found conflicting findings about the prevalence of erosive arthritis and the future development of RA in these patient groups.